Effect of slag on chloride resistance of concrete - Ahmad, S. (Springer Science and Business Media Deutschland GmbH, 2021)
The aim of this research work was to evaluate the performance of slag-mixed concrete, the resistance it would offer to chloride attack, and generally on the compressive strength of concrete. The cement was replaced with slag in different proportions. Concrete samples were prepared to have a slump between 90â120 mm with a constant water-binder ratio of 0.35. The material used for the replacement of cement was ground granulated blast-furnace slag (GGBS), it was replaced with Portland cement ranging from 10 to 50. A control mix with no slag was made in order to compare the results. The physical properties of the different samples were assessed through compressive strength tests whilst the durability characteristics were investigated in terms of chloride migration. The compressive strength tests confirmed that the compressive strength decreases with the increase in amount of slag in concrete. But the decrease in 28 days compressive strength varied from 18.72 MPa to 17.01 MPa for 50 replacement of cement with slag. The chloride migration tests confirmed that with the increase in replacement level of slag with Portland cement, there was an increase in chloride resistance. The penetration depth of chloride ions decreases from 27 mm to 3 mm. Migration coefficient decreases from 11.6, 10â12 m2 /s to 1.1, 10â12 m2/s. Therefore, slag offered more resistance to chloride attack at higher replacement levels and negligible effect on compressive strength. Â© The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2021.